2021
DOI: 10.1590/1984-0462/2021/39/2019317
|View full text |Cite
|
Sign up to set email alerts
|

Early Neonatal Near Miss in a University Hospital: Comparative Cross-Sectional Study

Abstract: Objective: To compare 2012 and 2016 data on early neonatal near miss indicators from Health Information Systems at a university hospital. Methods: This is a cross-sectional study conducted in 2012 and 2016. We considered early neonatal near misses the live births that presented one of the following risk conditions at birth: gestational age <33 weeks, birth weight <1,750g or 5-minute Apgar score <7, or Neonatal Intensive Care Unit (NICU) admission, and were alive until the 7th day of life. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
1
0
3
Order By: Relevance
“…As for the selection of criteria for the identification of cases of neonatal near miss adopted in this research, the main pragmatic entry criterion was gestational age <32 weeks, which was also identified by studies conducted in Maceió-AL 6 and in the South region of Ghana, Africa. 16 On the other hand, a research developed in Recife-PE, 17 identified low birth weight as the main isolated pragmatic entry criterion. It is noteworthy that both gestational age and low birth weight are factors associated with neonatal death.…”
Section: Discussionmentioning
confidence: 99%
“…As for the selection of criteria for the identification of cases of neonatal near miss adopted in this research, the main pragmatic entry criterion was gestational age <32 weeks, which was also identified by studies conducted in Maceió-AL 6 and in the South region of Ghana, Africa. 16 On the other hand, a research developed in Recife-PE, 17 identified low birth weight as the main isolated pragmatic entry criterion. It is noteworthy that both gestational age and low birth weight are factors associated with neonatal death.…”
Section: Discussionmentioning
confidence: 99%
“…Quanto à seleção dos critérios para a identificação dos casos de near miss neonatal adotados nesta pesquisa, o principal critério pragmático de entrada foi a idade gestacional <32 semanas, que também foi identificado pelos estudos realizados em Maceió-AL 6 e na região Sul de Gana, África. 16 Por sua vez, pesquisa desenvolvida em Recife-PE, 17 pragmático isolado de entrada, o baixo peso ao nascer. Ressalta-se que tanto a idade gestacional como o baixo peso ao nascer são fatores associados ao óbito neonatal.…”
Section: Discussionunclassified
“…Esses critérios foram validados 10,11 e tem 97% de sensibilidade, 92,6% de especificidade 9,10 e 97% de acurácia, 10,12 além de apresentarem os pontos de coorte mais adequados com base na literatura perinatal. 12 A partir das definições de critérios pragmáticos de NMN na literatura, este estudo testou a validade dos seguintes critérios no período neonatal (0 a 27 dias): peso de nascimento <1.500g, presença de anomalia congênita, idade gestacional (IG) menor que 32 semanas e Apgar<7 no quinto minuto, identificando especificidade de 97,70% [IC95%=97,55-97,84], sensibilidade de 80,07% [IC95%=75, 17] e uma acurácia de 97,57% [IC95%=97,41-97,71], apresentando uma alta sensibilidade e especificidade, assim como em estudos anteriores. Esse processo de validação usou os óbitos neonatais como padrão-ouro.…”
Section: Métodosunclassified
“…Resaltan que el modelo está orientado a predecir muertes neonatales, sin tener en cuenta la calidad de la atención, por lo que requiere complementarse si se va a utilizar con este fin (33,34). En concordancia, una revisión previa por la Dra.…”
Section: Discussionunclassified